Quality education The nexus of human capital development, economic growth and social justice in a South African context - Hove, Muchativugwa L. (AOSIS, 2021)
This book investigates the intersections between education, social justice, gendered violence and human rights in South African schools and universities. The rich and multifarious tapestry of scholarship and literature emanating from South African classrooms provides a fascinating lens through which we can understand the complex consequences of the economies of education, social justice imperatives, gendered violence on the lives of women and children, and marginalised communities. The scholarship in the book challenges readers to imagine alternative futures predicated on the transformational capacity of a democratic South Africa. Contributors to this volume examine the many ways in which social justice and gendered violence mirrors, expresses, projects and articulates the larger phenomenon of human rights violations in Africa and how, in turn, the discourse of human rights informs the ways in which we articulate, interrogate, conceptualise, enact and interpret quality education. The book also wrestles with the linguistic contradictions and ambiguities in the articulation of quality education in public and private spaces. This book is essential reading for scholars seeking solid grounding in exploring quality education, the instances of epistemic disobedience, the political implications of place and power, and human rights in theory and practice.